High-yield and high-performance porous biochar produced from pyrolysis of peanut shell with low-dose ammonium polyphosphate for chloramphenicol adsorption. (10th August 2020) - Yang, Jiwen; Ji, Guozhao; Gao, Yuan; Fu, Weng; Irfan, Muhammad; Mu, Lan; Zhang, Yulin; Li, Aimin
Abstract: Adsorptive removal by porous carbon materials has been considered an attractive technique to treat wastewater polluted by antibiotics. To produce porous biochar with high-yield and high-performance for chloramphenicol adsorption, this study prepared biochar from peanut shells using ammonium polyphosphate via pyrolysis. The combined effects of the main process parameters on biochar production were studied to determine the optimum operating conditions by response surface methodology based on Box-Behnken design. Low-dose ammonium polyphosphate has a significant positive effect on the yield, surface functional groups, pore volume, and surface area of biochar. This is caused by the richness of nitrogen and phosphorus in ammonium polyphosphate and its flame retardant property. The high-yield biochar with a surface area of 979 ± 25 m 2 /g was obtained at a mass ratio of ammonium polyphosphate/peanut shell of 0.55, at 650 °C with a retention time of 60 min. The as-prepared biochar exhibited excellent adsorption performance with a monolayer chloramphenicol adsorption capacity of 423.7 mg/g. This was due to the high surface area, micropores formed by nano-sized particles, and richness of N- and P-containing functional groups. The characterization before and after chloramphenicol adsorption indicated micro-pore-filling, Van der Waals force, π-π interaction, and hydrogen-bonding interaction are the main adsorption mechanisms of chloramphenicol adsorption on as-prepared biochar. This study offered new insights on the preparation of biochar from waste biomass for application in wastewater treatment. Graphical abstract: Image 1 Highlights: Low-dose ammonium polyphosphate has a significant positive effect on biochar. The optimal pyrolysis condition was determined by response surface methodology. High-yield (40.1%) and high surface area (979 m 2 /g) of biochar was achieved. High chloramphenicol adsorption capacity of 423.7 mg/g by this biochar was reached.